Diazepam and Its Disinfection Byproduct Promote the Early Development of Nervous System in Zebrafish Embryos. (30th November 2020) - Zhao, Xiaole; Huang, Xiaoyong; Shi, Jiachen; Zhu, Kui; Shao, Bing
Abstract : The widely used diazepam, as central nervous system inhibitor, has found to be ubiquitous in surface water and drinking water. Moreover, a series of byproducts such as 2-methylamino-5-chlorobenzophenone (MACB) were generated after the chlorine disinfection process. However, little information is available about the neurobiological effects of these emerging chemicals at low doses, especially on infants and children. Here, we exposed zebrafish ( Danio rerio ) embryos to diazepam and MACB at 0.05, 0.5, and 5 nM, which were equivalent to environmental levels. Both diazepam and MACB increased the somite number and promoted nervous development of transgenic zebrafish [Tg (elavl3: EGFP) larvae] at 72 hours postfertilization ( hpf). Both diazepam and MACB also disrupted the homeostasis of adenosine monophosphate, valine, methionine, and fumaric acid in zebrafish embryos at 12 hpf. Additionally, the locomotor behavior activity of zebrafish was significantly enhanced after 120-hour sustained exposure to diazepam or MACB. Moreover, the mRNA expression levels of oct4, sox2, and nanog, modulating the pluripotency and self-renewal, were upregulated by diazepam and MACB in zebrafish embryo. Altogether, diazepam and MACB stimulate developmental neurogenesis and may induce neuronal excitotoxicity at quite low doses. These results indicated that the chronic exposure to psychoactive drugs may pose a potential risk to the development of the nervous system in infancy.